Pengaruh Penyegaran Kader Terhadap Pengetahuan Dan Keterampilan Dalam Melaksanakan Tugas Kader Di Wilayah Kerja Puskesmas Karang Pule - Pipit Desyi Nur Octavia; Yuli Laraeni (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Kaders are community members who are willing, able and have time to organize volunteer Posyandu activities. The knowledge and skills of the cadres need to be improved especially on cadre tasks in posyandu activities so as to contribute well in organizing posyandu activities. The knowledge and skills of the cadres can be improved by providing cadre refreshment. Research Methods. This study was pre-experimental with one group pretest-posttest research design. The population in this study is all the cadres in Keluranah Karang Pule amounted to 44 people. Samples were taken using Simple Random Sampling technique amounted to 31 people. Data collection was conducted on 12 - 21 July 2017. Research Result. Knowledge and skills of cadres before being given refresher, 45% knowledge in sufficient category, skill use 19% dacin in the less skilled category, and skill of filling KMS 71% in skilled categories and 6% in unskilled category. Knowledge and skill after refreshing, 87% knowledge in good category, 100% dacin using skill in skilled category, and skill of KMS 81% in skilled category. Based on statistical test analysis Paired sample t-test showed that the result of paired sample t-test was obtained p <0,05. Conclusion. There is influence of cadre refresher on knowledge and skill in performing duty cadre in Work Area of Puskesmas Karang Pule.